2002
DOI: 10.1097/01.asn.0000022007.91733.62
|View full text |Cite
|
Sign up to set email alerts
|

The Leptospira Outer Membrane Protein LipL32 Induces Tubulointerstitial Nephritis-Mediated Gene Expression in Mouse Proximal Tubule Cells

Abstract: Abstract. Tubulointerstitial nephritis is a main renal manifestation caused by pathogenic leptospira that accumulate mostly in the proximal tubules, thereby inducing tubular injury and tubulointerstitial nephritis. To elucidate the role of leptospira outer membrane proteins in tubulointerstitial nephritis, outer membrane proteins from pathogenic Leptospira shermani and nonpathogenic Leptospira patoc extracted by Triton X-114 were administered to cultured mouse proximal tubule cells. A dose-dependent increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 34 publications
3
77
1
8
Order By: Relevance
“…The only significant difference observed between the Inos KO and the WT C57BL/6 mice was that the transgenic animals did not develop interstitial nephritis to the same degree or severity as the WT control. This result is in accordance with the hypothesis that the expression of proinflammatory markers by renal tubular cells in vitro after exposure to leptospiral products may be related to the development of interstitial nephritis in vivo (20)(21)(22). The present study confirms previous reports, using mice of other backgrounds (C3H and C3H/HeJ), that immunodeficiency results in high susceptibility to acute infection, rapidly progressing to death (14,19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The only significant difference observed between the Inos KO and the WT C57BL/6 mice was that the transgenic animals did not develop interstitial nephritis to the same degree or severity as the WT control. This result is in accordance with the hypothesis that the expression of proinflammatory markers by renal tubular cells in vitro after exposure to leptospiral products may be related to the development of interstitial nephritis in vivo (20)(21)(22). The present study confirms previous reports, using mice of other backgrounds (C3H and C3H/HeJ), that immunodeficiency results in high susceptibility to acute infection, rapidly progressing to death (14,19).…”
Section: Discussionsupporting
confidence: 93%
“…In vitro studies have previously reported the activation of a broad range of inflammatory genes, such as those for transcription factor NF-B, inducible nitric oxide synthase (iNOS), monocyte chemotactic protein-1, and tumor necrosis factor alpha, by renal tubular cells in response to exposure to leptospire-derived products. These findings have been interpreted as a molecular trigger for interstitial nephritis (20)(21)(22). The genetic deficiency of iNOS has not been investigated in vivo.…”
mentioning
confidence: 99%
“…15 Arterial hypotension is common. 16,17 The hemodynamic status and alterations in most patients with severe leptospirosis are similar to those observed in patients with sepsis. Because of systemic vasodilation, the plasma levels of aldosterone and antidiuretic hormone are high.…”
Section: Clinical Manifestationsmentioning
confidence: 80%
“…More recently, a realtime PCR was developed using TaqMan chemistry (Smythe et al, 2002) which targeted an 87 bp section of the 16S rRNA gene of Leptospira spp. In this study, we report the development of a real-time assay using SYBR green chemistry, in which the target is the gene for the major outer-membrane lipoprotein LipL32 (Haake et al, 2000), which appears to be an important virulence factor (Yang et al, 2002), confined to pathogenic strains of all Leptospira spp. †Present address: Saskatchewan Health, Provincial Laboratory, 3211 Albert Street, Regina, Saskatchewan, Canada S4S 5W6.…”
Section: Introductionmentioning
confidence: 99%